The Role of Histone Post-Translational Modifications in Merkel Cell Carcinoma - Mazziotta, Chiara; Lanzillotti, Carmen; Gafà, Roberta; Touzé, Antoine; Durand, Marie-Alice; Martini, Fernanda; Rotondo, John Charles (Frontiers in Oncology, 2022)
Merkel Cell Carcinoma (MCC) is a is a rare but highly aggressive form of non–melanoma skin cancer whose 5-year survival rate is 63%. Merkel cell polyomavirus (MCPyV), a small DNA tumor virus, is the etiological agent of MCC. Although representing a small proportion of MCC cases, MCPyV-negative MCCs have also been identified. The role of epigenetic mechanisms, including histone post-translational modifications (PTMs) in MCC, have been only partially determined. This review aims to describe the most recent progress on PTMs and their regulative factors in the context of MCC onset/development, providing an overview of current findings on both MCC subtypes. An outline of current knowledge on the potential employment of PTMs and related factors as diagnostic and prognostic markers, as well as novel treatment strategies targeting the reversibility of PTMs for MCC therapy is provided. Recent research shows that PTMs are emerging as important epigenetic players involved in MCC onset/development, and therefore may show a potential clinical significance. Deeper and integrated knowledge of currently known PTM dysregulations is of paramount importance in order to understand the molecular basis of MCC and improve the diagnosis, prognosis, and therapeutic options for this deadly tumor.